2009
DOI: 10.1111/j.1349-7006.2008.01048.x
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin‐7 interacts with melanoma inhibitory activity protein and negatively modulates melanoma cell migration

Abstract: Melanoma inhibitory activity (MIA) has been identified as a small protein secreted from malignant melanoma cells, which strongly enhances melanoma cell migration and invasion. Detailed analyses performed by our group showed interaction of MIA with extracellular matrix proteins and integrin a4b1 and a5b1 leading to cellular detachment. In this study, we identified cadherin-7 as a new MIA-binding protein using surface-enhanced laser desorption/ ionization-mass spectrometry technology and co-immunoprecipitation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
(34 reference statements)
0
20
1
Order By: Relevance
“…It was shown that CDH7 plays a role in tumor development of malignant melanoma cells by interacting with melanoma inhibitory activity protein (MIA) and migration melanoma cell [41]. …”
Section: Resultsmentioning
confidence: 99%
“…It was shown that CDH7 plays a role in tumor development of malignant melanoma cells by interacting with melanoma inhibitory activity protein (MIA) and migration melanoma cell [41]. …”
Section: Resultsmentioning
confidence: 99%
“…The MIA protein, the secreted inhibitor of cell growth, prevents the attachment of melanoma cells to the extracellular matrix, thus promoting invasion and metastazing [32–34]. As opposed to the TYR gene promoter, the activity of the human MIA gene promoter correlates with melanoma progression [35].…”
Section: Promoters That Are Specifically Active In Melanocytesmentioning
confidence: 99%
“…Recombinant MIA inhibits melanoma cell growth and cell attachment in vitro [16]. Subsequent studies revealed that MIA interacts with extracellular matrix components, laminin and fibronectin, as well as with cellular matrix receptors integrin α5, integrin α4 [17] and cadherin 7 [18]. …”
Section: Introductionmentioning
confidence: 99%